2022
DOI: 10.1002/acr2.11408
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccine Hesitancy and Its Determinants Among Rheumatology Patients

Abstract: Objective Patients with rheumatic disease (RD) have an increased risk of influenza and its complications. Despite inactivated influenza vaccine (IIV) recommendations, IIV uptake in patients with RD is suboptimal, a problem of increasing importance in the COVID‐19 era. We estimated the frequency of IIV hesitancy and associated factors among Canadian patients with RD. Methods A cross‐sectional vaccine hesitancy survey was completed by rheumatology clinic patients (November 2019 to January 2020). Patients rated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Sixty-one studies reported perceived barriers to receiving an influenza vaccination in the total population ( Table 4 ) [ 16 , 17 , 19 , 21 , 22 , 23 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 40 , 41 , 43 , 45 , 46 , 47 , 48 , 49 , 50 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sixty-one studies reported perceived barriers to receiving an influenza vaccination in the total population ( Table 4 ) [ 16 , 17 , 19 , 21 , 22 , 23 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 40 , 41 , 43 , 45 , 46 , 47 , 48 , 49 , 50 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , …”
Section: Resultsmentioning
confidence: 99%
“…Barrier types were further assessed to determine the key factors (determined by agreement rate) across the general and unvaccinated population for not receiving an influenza vaccine. The top-five barriers to influenza vaccination, as reported by the total population compared to the unvaccinated population, are illustrated in Figure 3 [ 16 , 17 , 19 , 21 , 22 , 23 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 40 , 41 , 43 , 45 , 46 , 47 , 48 , 49 , 50 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the recent vaccination guidelines, understanding the barriers to vaccine uptake from the perspective of individuals with RMDs, and implementing specific strategies to address them is crucial 8 , 9 . Vaccine-hesitancy, vaccine-avoidance and vaccine-refusal have increased since the COVID-19 pandemic and are amplified by misinformation promoted by social media platforms 10 .…”
mentioning
confidence: 99%